Pengaruh Penggunaan Bahasa Sunda Terhadap Tingkat Pemahaman Mahasiswa Luar Sunda - Ferry Dinata; Firda Kristyani Avela; Rizka Rahmalia; Windy Ariyanti (LP3M KH Yazid Karimullah Institute, 2024)
Language acts as a tool of social integration as well as a tool of social adaptation. Sundanese is one of the regional languages in Indonesia. However, the use of Sundanese must be adjusted to the place and the person speaking. But in reality, there are still many students and lecturers who speak Sundanese when the learning process in the classroom takes place. Practically, this research is expected to build awareness in communicating between people to always use Indonesian in their daily lives so that everyone can understand both when interacting with peers or lecturers. The researcher used a qualitative approach with in-depth interviewing method. Interviews were conducted with open-ended questions addressed to students of the University of Education Indonesia Geography Education Study Program Batch 2023 who came from outside Sundanese areas. The results of this study are that students who come from outside Sundanese areas have difficulty in understanding the material when there are sentence inserts or Sundanese vocabulary in its delivery. This can be overcome by asking friends who understand Sundanese, following the flow of learning so that gradually they will get used to and understand Sundanese. They do this to be able to understand every material delivered by the lecturer when inserting words in Sundanese.